Beyond the Economic Crisis: CO2lonialism and Geographies of Hope - Hazlewood, Julianne (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2010)
This paper takes us beyond the present economic crisis to where global warming warns of a much more profound problem: a structural flaw in capitalism. Theoretically linking relations between climate change, colonialism, and capitalism, San Lorenzo is investigated as an agricultural frontier where “CO2lonialism” unfolds in African oil palm cultivation and agrofuel production. This re s e a rch highlights the cultural and spatial practices through which Afro - Ecuadorian, Chachi and Awá communities construct and sustain “geographies of hope” amid landscapes of fallen forests, poisoned rivers and social conflicts. Expounding on the ecological debt of the Global No rth to the Global South, this paper condemns discourses and actions that solely focus on improving the economic climate while bulldozing rainforests, livelihoods, and real solutions to climate change.